2010
DOI: 10.1111/j.1751-7133.2010.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Reduction With β‐Blockers in Ischemic Cardiomyopathy Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Coronary artery bypass grafting (CABG) in patients with systolic heart failure (HF) carries high morbidity and mortality rates. Reducing perioperative mortality with beta-blockers (BBs) may help improve outcomes. Analysis of 4903 patients who underwent isolated CABG surgery was performed. In-hospital mortality of systolic HF patients who received BBs was 2.03%; systolic HF patients who did not receive BBs had a mortality of 5.20%. Thirty-day mortality was 2.98% in the patients with systolic HF who received BBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
1
Order By: Relevance
“…Because of the great heterogeneity of the studies, the random-effects model and sensitivity analyses approach were selected and 3 studies (Terence Lin (7), William E. Boden (8) and Michelle M (14)) were excluded. Also, the impact of removing each of the studies was evaluated in the summary results but the results did not change.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the great heterogeneity of the studies, the random-effects model and sensitivity analyses approach were selected and 3 studies (Terence Lin (7), William E. Boden (8) and Michelle M (14)) were excluded. Also, the impact of removing each of the studies was evaluated in the summary results but the results did not change.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a preoperative beta-blockade in patients with reduced LVEF, continuing beta-blockers during the early postoperative phase has also been shown to significantly reduce the 30day mortality rate following CABG [170]. Strong evidence suggests that beta-blockers reduce the number of deaths in patients with a recent MI or reduced LVEF (<35%) [171,172].…”
Section: Postoperative Beta-blockersmentioning
confidence: 99%
“…Evidence for ACEi has been discussed previously and little data exists for β-blockers. In 2010, Lin et al 72 reported improvements in mortality both in-hospital and at 30 days in 1369 post-CABG patients with EF < 40%. However, Ferguson et al (2002) 63 reported a trend toward increased 30-day mortality in patients with EF < 30%.…”
Section: Patients With LV Dysfunctionmentioning
confidence: 99%